A lithium iron phosphate composite material and preparation method thereof
By modifying lithium iron phosphate positive electrode materials, including doped Ni and V elements, carbon coating and MXene/PPy nanomaterial loading, the low ion diffusion rate and conductivity of lithium iron phosphate materials in lithium-ion batteries is solved, and its electrochemical performance and cycling performance are significantly improved.
Patent Information
- Application Number
- CN202410742249.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-06-11
AI Technical Summary
The application of lithium iron phosphate positive electrode material in lithium-ion batteries is limited by its disadvantages such as low ion diffusion rate and low electronic conductivity, and requires modification processing to improve electrochemical performance, cycling performance and rate performance.
FePO4 precursors are synthesized by hydrothermal synthesis, Ni and V elements doped, first layer and secondary carbon coating are carried out, LiFe(1-x-y)VxNiyPO4/C nanomaterial is synthesized, and the MXene/PPy nanomaterial is used as the substrate for polypyrrole loading. Finally, LiFe(1-x-y)VxNiyPO4/C nanomaterial is composited with MXene/PPy nanomaterial to prepare lithium iron phosphate composite material.
The cycling performance, rate performance and electrochemical performance of lithium iron phosphate composite materials have been significantly improved, including improving the diffusion rate of lithium ion, structural stability, conductivity and electrochemical performance.
Smart Images

Figure BDA0004885210630000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron phosphate composite material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have a series of advantages such as high specific capacity, high operating voltage, good safety, and no memory effect. They are widely used in many portable electronic instruments and equipment such as laptops, mobile phones, and instruments. The decisive factor restricting the capacity of lithium-ion batteries is the positive electrode material. At present, the most studied lithium-ion battery positive electrode materials on the market are lithium manganese oxide (LiMn2O4), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO4), lithium iron phosphate (LiFePO4) and other materials. However, compared with lithium iron phosphate, lithium cobalt oxide is expensive, lithium nickel oxide has poor stability under high temperature conditions, and lithium manganese oxide has a fast capacity decay during long-term charging and discharging. These shortcomings of positive electrode materials limit their application in lithium-ion batteries.
[0003] Lithium iron phosphate cathode materials have many advantages, such as low price, non-toxicity, no pollution to the environment, wide source of raw materials, good thermal stability, long life, good electrochemical performance and safety performance, good overcharge resistance, etc. These advantages make the application of lithium iron phosphate cathode materials in power batteries attract much attention. However, with the increasing market requirements for lithium-ion battery performance, the shortcomings of lithium iron phosphate cathode materials such as low ion diffusion rate and low electronic conductivity have limited the application of lithium iron phosphate in lithium-ion batteries. It needs to be modified (such as element doping, carbon coating, composite materials, etc.) to improve its electrochemical performance, cycle performance and rate performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a lithium iron phosphate composite material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a lithium iron phosphate composite material comprises the following steps:
[0007] Step S1: Add ferric chloride hexahydrate to deionized water and stir and mix evenly, which is recorded as solution A. Stir and mix evenly in a reactor containing ammonium dihydrogen phosphate and deionized water, then add solution A to the reactor and mix and stir evenly, and adjust the pH of the system to 2.0-2.5, continue stirring for 30 minutes, transfer the mixed solution to an autoclave, and react at 130-150°C for 10 hours. After cooling to room temperature, centrifuge, wash, and vacuum dry at 80°C for 24 hours to obtain a FePO4 precursor;
[0008] Specifically, in step S1, the usage ratio of ammonium dihydrogen phosphate, deionized water and solution A is 0.01-0.03 mol: 20 mL: 20 mL;
[0009] Specifically, the dosage ratio of ferric chloride hexahydrate to deionized water in solution A is 0.01-0.03 mol:20 mL.
[0010] Step S2: According to the Li:P molar ratio = 1:1, 0.5g of FePO4 precursor and 0.146g of lithium hydroxide monohydrate were weighed and ground for 10min, then ammonium metavanadate, nickel hydroxide and 5mL of anhydrous ethanol were added to a mortar and ground for 30min, and then 0.0636g of ascorbic acid was added and ground for another 10min, and then the mixture was transferred to a tubular furnace with argon gas, heated to 350℃ at a rate of 5℃ / min, calcined for 5h, and cooled to room temperature to obtain LiFe (1-x-y) V x Ni y PO4 nanomaterials;
[0011] Specifically, the amounts of ammonium metavanadate and nickel hydroxide are weighed according to the molar ratio of Fe:V:Ni=0.95-1:0.01-0.03:0.01-0.02;
[0012] Specifically, LiFe (1-x-y) V x Ni y In PO4 nanomaterials, x is 0.01-0.03 and y is 0.01-0.02.
[0013] Step S3: Add the above LiFe (1-x-y) V x Ni y The PO4 nanomaterial is transferred to a mortar, and then lignin is added and ground for 10-20 minutes. The mixture is placed in a tube furnace with argon gas and calcined at 600-700℃ for 8-12 hours. After the reaction is completed, it is cooled to room temperature to obtain LiFe (1-x-y) V x Ni y PO4 / C nanomaterials;
[0014] Specifically, the mass of lignin is 0.03-0.05 g.
[0015] Step S4: Add the MXene nanosheets and p-toluenesulfonic acid after HCl-LiF etching into a reactor containing deionized water, and ultrasonically treat for 30-50 minutes. Then place the reactor in an ice water bath, add pyrrole monomer and stir for 30-45 minutes, add 1 mol / L ammonium peroxodisulfate aqueous solution and continue stirring for 8-10 hours. After the reaction is completed, centrifuge, wash, and freeze-dry to obtain MXene / PPy nanomaterials;
[0016] Specifically, the usage ratio of the MXene nanosheets after HCl-LiF etching, p-toluenesulfonic acid, deionized water, pyrrole monomer and ammonium peroxodisulfate aqueous solution is 0.1-0.3 g: 0.08-0.24 g: 30 mL: 0.08-0.2 g: 5-10 mL.
[0017] Step S5: Stir and mix the MXene / PPy nanomaterials in deionized water, which is referred to as solution B, and then add LiFe (1-x-y) V x Ni y PO4 / C nanomaterials and hexadecyltrimethylammonium bromide are dispersed in deionized water, and after ultrasonic treatment for 20 minutes, solution B is slowly added at a speed of 800-1000 rpm. After the addition is completed, stirring is continued for 10-20 minutes, centrifugation, washing, and freeze-drying are performed to obtain a lithium iron phosphate composite material;
[0018] Specifically, LiFe (1-x-y) V x Ni y The dosage ratio of PO4 / C nanomaterial, hexadecyltrimethylammonium bromide, deionized water and solution B is 1-2 g: 0.1-0.2 g: 250 mL: 5 mL, and the dosage ratio of MXene / PPy nanomaterial and deionized water in solution B is 0.015-0.045-0.09 g: 5 mL.
[0019] The invention also discloses a lithium iron phosphate composite material obtained by the preparation method.
[0020] Beneficial effects of the present invention:
[0021] The lithium iron phosphate composite material prepared by the present invention has excellent cycle performance, rate performance and electrochemical performance. The composite material is modified based on lithium iron phosphate, (1) hydrothermally synthesizing a FePO4 precursor; (2) doping the FePO4 precursor with Ni and V, and using ascorbic acid as a carbon source to achieve a first layer of carbon coating to synthesize LiFe (1-x-y) V x Ni y PO4 nanomaterials; (3) Using lignin as a carbon source to achieve secondary coating synthesis of LiFe (1-x-y) V x Ni y PO4 / C nanomaterials; (4) Using MXene nanosheets as the substrate, polypyrrole is loaded on the surface and between the layers to synthesize MXene / PPy nanomaterials; (5) Using surfactants, LiFe (1-x-y) V x Ni yPO4 / C nanomaterials and MXene / PPy nanomaterials are composited to prepare lithium iron phosphate composite materials.
[0022] Firstly, FePO4 precursor was hydrothermally synthesized using ferric chloride hexahydrate and ammonium dihydrogen phosphate as phosphoric acid raw materials; secondly, Ni and V elements were doped on the basis of FePO4 precursor and LiFe (1-x-y) V x Ni y PO4 nanomaterials, by doping Ni and V, make the two work together to increase the lattice volume of lithium iron phosphate, prevent the generation of iron / lithium reaction defects, and make Li + The migration channel becomes wider, thereby improving the lithium ion diffusion rate and the structural stability of lithium iron phosphate, further improving the electrochemical performance of lithium iron phosphate; in addition, the amorphous carbon produced by the decomposition of ascorbic acid at high temperature is used as the first layer of carbon coating to improve the conductivity and electrochemical performance of lithium iron phosphate. At the same time, it can also inhibit the growth of lithium iron phosphate and reduce the size of lithium iron phosphate, thereby shortening the diffusion path of lithium ions, promoting the diffusion rate of lithium ions, and improving the electrochemical performance of the material. Thirdly, lignin is used as the carbon source for secondary carbon coating to synthesize LiFe (1-x-y) V x Ni yPO4 / C nanomaterials, referred to as lithium iron phosphate particles, have a higher tap density due to the secondary coating of carbon, which further improves the electrochemical performance of the material. Then, pyrrole was used as a monomer and MXene nanosheets etched with HCl-LiF were used as the substrate. The MXene / PPy nanomaterials were synthesized by in-situ polymerization. Polypyrrole was loaded on the surface and interlayer of the MXene nanosheets, which increased the interlayer spacing of the MXene / PPy nanomaterials and improved the electrochemical performance of the MXene / PPy nanomaterials. This is because the polypyrrole loading increases the specific surface area of the material, increases the contact area between the material and the electrolyte ions, and increases the ion transfer rate, thereby improving the electrochemical performance of the material. The nitrogen-containing functional groups in polypyrrole can improve the conductivity of the composite material, accelerate ion transmission, and further improve the electrochemical performance of the composite material. Finally, the MXene / PPy nanomaterials were compounded with lithium iron phosphate particles using surfactants to obtain lithium iron phosphate composite materials; under the action of the surfactant hexadecyltrimethylammonium bromide, the lithium iron phosphate particles accumulated on the MXene / PPy nanomaterial skeleton to form porous composite particles. The skeleton constructed by the MXene / PPy nanomaterial can accelerate the ion and electron transmission between lithium iron phosphate particles, thereby improving the rate performance of the composite material. The lithium iron phosphate particles are embedded in the skeleton, which can effectively prevent the agglomeration of lithium iron phosphate particles, and at the same time increase the contact area between the electrolyte and the lithium iron phosphate particles, ensuring the rapid transfer of ions and providing more active sites for redox reactions; the macromolecular action of the surfactant can maintain the structure of the lithium iron phosphate composite material from being destroyed, so that the composite material always maintains an efficient and stable ion and electron transmission network structure in the electrochemical reaction, and improves the cycle performance of the composite material. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] A method for preparing a lithium iron phosphate composite material comprises the following steps:
[0026] Step S1: Add 0.01 mol of ferric chloride hexahydrate to 20 mL of deionized water and stir to mix evenly, which is recorded as solution A. Add 0.01 mol of ammonium dihydrogen phosphate containing 20 mL of deionized water in a reactor and stir to mix evenly, then add 20 mL of solution A into the reactor and stir to mix evenly, and adjust the pH of the system to 2.0, continue stirring for 30 minutes, transfer the mixed solution to an autoclave, and react at 130-150° C. for 10 hours. After cooling to room temperature, centrifuge, wash, and vacuum dry at 80° C. for 24 hours to obtain a FePO4 precursor;
[0027] Step S2: According to the Li:P molar ratio = 1:1, 0.5g of FePO4 precursor and 0.146g of lithium hydroxide monohydrate were weighed and ground for 10min, then ammonium metavanadate, nickel hydroxide and 5mL of anhydrous ethanol were added to a mortar and ground for 30min, and then 0.0636g of ascorbic acid was added and ground for another 10min, and then the mixture was transferred to a tubular furnace with argon gas, heated to 350℃ at a rate of 5℃ / min, calcined for 5h, and cooled to room temperature to obtain LiFe 0.96 V 0.03 Ni 0.01 The amounts of PO4 nanomaterials, ammonium metavanadate and nickel hydroxide were weighed according to the molar ratio of Fe:V:Ni=0.96:0.03:0.01;
[0028] Step S3: Add the above LiFe 0.96 V 0.03 Ni 0.01 The PO4 nanomaterial was transferred to a mortar, and 0.03 g of lignin was added and ground for 10 min. The mixture was placed in a tube furnace with argon gas and calcined at 600 ° C for 8 h. After the reaction was completed, it was cooled to room temperature to obtain LiFe 0.96 V 0.03 Ni 0.01 PO4 / C nanomaterials;
[0029] Step S4: 0.1 g of MXene nanosheets etched with HCl-LiF (prepared according to the method of CN115041027B patent) and 0.08 g of p-toluenesulfonic acid were added to a reactor containing 30 mL of deionized water, and ultrasonic treatment was performed for 30 min. The reactor was then placed in an ice water bath, and 0.08 g of pyrrole monomer was added and stirred for 30 min. 5 mL of 1 mol / L ammonium peroxodisulfate aqueous solution was added dropwise and continued to stir for 8 h. After the reaction was completed, the mixture was centrifuged, washed, and freeze-dried to obtain MXene / PPy nanomaterials.
[0030] Step S5: 0.015 g of MXene / PPy nanomaterials were stirred and mixed in 5 mL of deionized water, which was recorded as solution B. Then 1 g of LiFe 0.96 V0.03 Ni 0.01 PO4 / C nanomaterials and 0.1 g hexadecyltrimethylammonium bromide were dispersed in 250 mL of deionized water. After ultrasonic treatment for 20 min, 5 mL of solution B was slowly added at a speed of 800 rpm. After the addition was completed, stirring was continued for 10 min, and the mixture was centrifuged, washed, and freeze-dried to obtain a lithium iron phosphate composite material.
[0031] Example 2
[0032] A method for preparing a lithium iron phosphate composite material comprises the following steps:
[0033] Step S1: Add 0.02 mol of ferric chloride hexahydrate to 20 mL of deionized water and stir to mix evenly, which is recorded as solution A. Add 0.02 mol of ammonium dihydrogen phosphate containing 20 mL of deionized water in a reactor and stir to mix evenly. Then add 20 mL of solution A to the reactor and stir to mix evenly. Adjust the pH of the system to 2.0, continue stirring for 30 min, transfer the mixed solution to an autoclave, and react at 140 ° C for 10 h. After cooling to room temperature, centrifuge, wash, and vacuum dry at 80 ° C for 24 h to obtain a FePO4 precursor.
[0034] Step S2: According to the Li:P molar ratio = 1:1, 0.5g of FePO4 precursor and 0.146g of lithium hydroxide monohydrate were weighed and ground for 10min, then ammonium metavanadate, nickel hydroxide and 5mL of anhydrous ethanol were added to a mortar and ground for 30min, and then 0.0636g of ascorbic acid was added and ground for another 10min, and then the mixture was transferred to a tubular furnace with argon gas, heated to 350℃ at a rate of 5℃ / min, calcined for 5h, and cooled to room temperature to obtain LiFe 0.96 V 0.02 Ni 0.02 The amounts of PO4 nanomaterials, ammonium metavanadate and nickel hydroxide were weighed according to the molar ratio of Fe:V:Ni=0.96:0.02:0.02;
[0035] Step S3: Add the above LiFe 0.96 V 0.02 Ni 0.02 The PO4 nanomaterial was transferred to a mortar, and 0.04 g of lignin was added and ground for 15 min. The mixture was placed in a tube furnace with argon gas and calcined at 650 ° C for 10 h. After the reaction was completed, it was cooled to room temperature to obtain LiFe 0.96 V 0.02 Ni 0.02 PO4 / C nanomaterials;
[0036] Step S4: 0.2 g of MXene nanosheets etched with HCl-LiF (prepared according to the method of CN115041027B patent) and 0.16 g of p-toluenesulfonic acid were added to a reactor containing 30 mL of deionized water, and ultrasonic treatment was performed for 40 min. The reactor was then placed in an ice water bath, and 0.15 g of pyrrole monomer was added and stirred for 30 min. 7 mL of 1 mol / L ammonium peroxodisulfate aqueous solution was added dropwise and continued to stir for 9 h. After the reaction was completed, centrifugation, washing, and freeze-drying were performed to obtain MXene / PPy nanomaterials.
[0037] Step S5: 0.045 g of MXene / PPy nanomaterial was stirred and mixed in 5 mL of deionized water, which was recorded as solution B. Then 1.5 g of LiFe 0.96 V 0.02 Ni 0.02 PO4 / C nanomaterials and 0.15 g hexadecyltrimethylammonium bromide were dispersed in 250 mL deionized water. After ultrasonic treatment for 20 min, 5 mL of solution B was slowly added at a speed of 900 rpm. After the addition was completed, stirring was continued for 15 min, and the mixture was centrifuged, washed, and freeze-dried to obtain a lithium iron phosphate composite material.
[0038] Example 3
[0039] A method for preparing a lithium iron phosphate composite material comprises the following steps:
[0040] Step S1: Add 0.03 mol of ferric chloride hexahydrate to 20 mL of deionized water and stir to mix evenly, which is recorded as solution A. Add 0.03 mol of ammonium dihydrogen phosphate containing 20 mL of deionized water in a reactor and stir to mix evenly. Then add 20 mL of solution A to the reactor and stir to mix evenly. Adjust the pH of the system to 2.5, continue stirring for 30 min, transfer the mixed solution to an autoclave, and react at 150 ° C for 10 h. After cooling to room temperature, centrifuge, wash, and vacuum dry at 80 ° C for 24 h to obtain a FePO4 precursor.
[0041] Step S2: According to the Li:P molar ratio = 1:1, 0.5g of FePO4 precursor and 0.146g of lithium hydroxide monohydrate were weighed and ground for 10min, then ammonium metavanadate, nickel hydroxide and 5mL of anhydrous ethanol were added to a mortar and ground for 30min, and then 0.0636g of ascorbic acid was added and ground for another 10min, and then the mixture was transferred to a tubular furnace with argon gas, heated to 350℃ at a rate of 5℃ / min, calcined for 5h, and cooled to room temperature to obtain LiFe 0.97 V 0.01 Ni 0.02 The amounts of PO4 nanomaterials, ammonium metavanadate and nickel hydroxide were weighed according to the molar ratio of Fe:V:Ni=0.97:0.02:0.02;
[0042] Step S3: Add the above LiFe 0.97 V 0.01 Ni 0.02 The PO4 nanomaterial was transferred to a mortar, and 0.05 g of lignin was added and ground for 20 min. The mixture was placed in a tube furnace with argon gas and calcined at 700 ° C for 12 h. After the reaction was completed, it was cooled to room temperature to obtain LiFe 0.97 V 0.01 Ni 0.02 PO4 / C nanomaterials;
[0043] Step S4: 0.3 g of MXene nanosheets etched with HCl-LiF (prepared according to the method of CN115041027B patent) and 0.24 g of p-toluenesulfonic acid were added to a reactor containing 30 mL of deionized water, and ultrasonic treatment was performed for 50 min. The reactor was then placed in an ice water bath, and 0.2 g of pyrrole monomer was added and stirred for 45 min. 10 mL of 1 mol / L ammonium peroxodisulfate aqueous solution was added dropwise and continued to stir for 10 h. After the reaction was completed, the mixture was centrifuged, washed, and freeze-dried to obtain MXene / PPy nanomaterials.
[0044] Step S5: 0.09 g of MXene / PPy nanomaterials were stirred and mixed in 5 mL of deionized water, which was recorded as solution B. Then 2 g of LiFe 0.97 V 0.01 Ni 0.02 PO4 / C nanomaterials and 0.2 g of hexadecyltrimethylammonium bromide were dispersed in 250 mL of deionized water. After ultrasonic treatment for 20 min, 5 mL of solution B was slowly added at a speed of 1000 rpm. After the addition was completed, stirring was continued for 20 min, and the mixture was centrifuged, washed, and freeze-dried to obtain a lithium iron phosphate composite material.
[0045] Comparative Example 1
[0046] This comparative example is a lithium iron phosphate composite material, which is different from Example 3 in that V ions and Ni ions are not doped, and the rest are the same.
[0047] Comparative Example 2
[0048] This comparative example is a lithium iron phosphate composite material. Compared with Example 3, the difference is that the lithium iron phosphate material is not coated with carbon material, and the rest is the same.
[0049] Comparative Example 3
[0050] This comparative example is a lithium iron phosphate composite material. Compared with Example 3, the difference is that the MXene nanosheets are not loaded with PPy, and the rest are the same.
[0051] The electrochemical performance of the lithium iron phosphate composite material samples prepared in Examples 1-3 and Comparative Examples 1-3 was tested.
[0052] Test method: Mix the lithium iron phosphate composite material prepared in Examples 1-3 and Comparative Examples 1-3 with conductive carbon black and PVDF in a mass ratio of 90:5:5, add an appropriate amount of 1-methyl-2-pyrrolidone and ball-mill for 1 hour to make a slurry, evenly apply it on an aluminum sheet, dry and press it into a positive electrode sheet, assemble it into a button battery with a metal lithium sheet as the negative electrode, and test the electrical performance at a voltage of 2.75V to 4.25V and a constant current of 0.2C for charge / discharge. The test results are as follows:
[0053]
[0054] It can be seen from the above table that the lithium iron phosphate composite material prepared by the present invention has higher first discharge capacity and first efficiency, indicating that the gram capacity of the composite material is improved, and the improvement of the lithium ion transfer rate shows a higher first efficiency. At the same time, after 100 cycles, the capacity retention rate of the composite material is 95.8%-97.7%, indicating that the composite material has excellent cycle performance.
[0055] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a lithium iron phosphate composite material, characterized in that: The following steps are involved: Step S1: Add ferric chloride hexahydrate to deionized water and stir and mix evenly, which is recorded as solution A. Add ammonium dihydrogen phosphate to a reactor containing deionized water and stir and mix evenly, then add solution A to the reactor and stir and mix evenly, and adjust the pH of the system to 2.0-2.5, continue stirring for 30 minutes, transfer the mixed solution to an autoclave, and react at 130-150°C for 10 hours, cool to room temperature, centrifuge, wash, and vacuum dry at 80°C for 24 hours to obtain a FePO4 precursor; Step S2: According to the Li:P molar ratio = 1:1, 0.5g of FePO4 precursor and 0.146g of lithium hydroxide monohydrate were weighed and ground for 10min, then ammonium metavanadate, nickel hydroxide and 5mL of anhydrous ethanol were added to a mortar and ground for 30min, and then 0.0636g of ascorbic acid was added and ground for another 10min, and then the mixture was transferred to a tubular furnace with argon gas, heated to 350℃ at a rate of 5℃ / min, calcined for 5h, and cooled to room temperature to obtain LiFe (1-x-y) V x Ni y PO4 nanomaterials, LiFe (1-x-y) V x Ni y In PO4 nanomaterials, x is 0.01-0.03 and y is 0.01-0.02; Step S3: Add the above LiFe (1-x-y) V x Ni y The PO4 nanomaterial is transferred to a mortar, and then lignin is added and ground for 10-20 minutes. The mixture is placed in a tube furnace with argon gas and calcined at 600-700℃ for 8-12 hours. After the reaction is completed, it is cooled to room temperature to obtain LiFe (1-x-y) V x Ni y PO4 / C nanomaterials; Step S4: Add the MXene nanosheets and p-toluenesulfonic acid after HCl-LiF etching into a reactor containing deionized water, and ultrasonically treat for 30-50 minutes. Then place the reactor in an ice water bath, add pyrrole monomer and stir for 30-45 minutes, add 1 mol / L ammonium peroxodisulfate aqueous solution and continue stirring for 8-10 hours. After the reaction is completed, centrifuge, wash, and freeze-dry to obtain MXene / PPy nanomaterials; Step S5: Stir and mix the MXene / PPy nanomaterials in deionized water, which is referred to as solution B, and then add LiFe (1-x-y) V x Ni y PO4 / C nanomaterials and hexadecyltrimethylammonium bromide were dispersed in deionized water. After ultrasonic treatment for 20 minutes, solution B was slowly added at a speed of 800-1000 rpm. After the addition was completed, stirring was continued for 10-20 minutes, centrifuged, washed, and freeze-dried to obtain a lithium iron phosphate composite material.
2. The method for preparing a lithium iron phosphate composite material according to claim 1, characterized in that: In step S1, the usage ratio of ammonium dihydrogen phosphate, deionized water and solution A is 0.01-0.03 mol: 20 mL: 20 mL.
3. The method for preparing a lithium iron phosphate composite material according to claim 2, characterized in that: The dosage ratio of ferric chloride hexahydrate to deionized water in solution A is 0.01-0.03 mol:20 mL.
4. The method for preparing a lithium iron phosphate composite material according to claim 1, characterized in that: In step S2, the amounts of ammonium metavanadate and nickel hydroxide are weighed according to the molar ratio of Fe:V:Ni=0.95-1:0.01-0.03:0.01-0.
02.
5. The method for preparing a lithium iron phosphate composite material according to claim 1, characterized in that: The mass of lignin in step S3 is 0.03-0.05 g.
6. The method for preparing a lithium iron phosphate composite material according to claim 1, characterized in that: In step S4, the usage ratio of the MXene nanosheets after HCl-LiF etching, p-toluenesulfonic acid, deionized water, pyrrole monomer and ammonium peroxodisulfate aqueous solution is 0.1-0.3 g: 0.08-0.24 g: 30 mL: 0.08-0.2 g: 5-10 mL.
7. The method for preparing a lithium iron phosphate composite material according to claim 1, characterized in that: In step S5, LiFe (1-x-y) V x Ni y The dosage ratio of PO4 / C nanomaterial, hexadecyltrimethylammonium bromide, deionized water and solution B is 1-2g: 0.1-0.2 g: 250 mL: 5 mL, and the dosage ratio of MXene / PPy nanomaterials and deionized water in solution B is 0.015-0.045-0.09 g: 5 mL.
8. A lithium iron phosphate composite material, characterized in that: The lithium iron phosphate composite material is prepared according to the method according to any one of claims 1-7.
Citation Information
Patent Citations
A dual-regulated two-dimensional MXene composite film and its preparation method
CN115041027B
LiFe1-xMxPO4 compound containing carbon element and preparation method thereof
CN102064317A
High-performance lithium iron phosphate cathode material and preparation method of lithium iron phosphate cathode material
CN103123968A